A ratiometric fluorescent probe for real-time monitoring of intracellular glutathione fluctuations in response to cisplatin. Issue 32 (4th August 2020) - Liu, Hanzhuang; Song, Wenting; Zhang, Shuren; Chan, Kin Shing; Guo, Zijian; Shen, Zhen
Abstract : Real-time imaging of intracellular glutathione in response to cisplatin by a ratiometric fluorescent probe reveals that the different trends in intracellular GSH levels is crucial in distinguishing cisplatin-resistant from cisplatin-sensitive cells. Abstract : Real-time imaging of fluctuations in intracellular glutathione (GSH) concentrations is critical to understanding the mechanism of GSH-related cisplatin-resistance. Here, we describe a ratiometric fluorescence probe based on a reversible Michael addition reaction of GSH with the vinyl-functionalized boron-dipyrromethene (4, 4-difluoro-4-bora-3 a, 4 a -diaza- s -indacene or BODIPY) 1 . The probe was applied for real-time monitoring of the fluctuations in GSH levels in cells under cisplatin treatment. Notably, in cellular cisplatin-sensitive A549 cells, GSH concentrations rose until cell death, while in cisplatin-resistant cell lines, GSH levels first rose to the maximum then fell back to the initial concentration without significant apoptosis. These results indicate that different trends in GSH fluctuation can help distinguish cisplatin-resistant from cisplatin-sensitive cells. As such, this study has shown that probe 1 may potentially be used for real-time monitoring of intracellular GSH levels in response to therapeutics.